Liquid-phase synthesis of the Li10GeP2S12-type phase in the Li–Si–P–S–Cl system. Issue 27 (29th June 2022) - Ito, Tomohiro; Hori, Satoshi; Hirayama, Masaaki; Kanno, Ryoji
Abstract : A new liquid-phase synthesis of the Li10 GeP2 S12 -type phase in the Li–Si–P–S–Cl system, which shows the highest lithium ionic conductivity among the reported Li-ion conductors, was developed for large-scale production. Abstract : The Li10 GeP2 S12 -type phase in the Li–Si–P–S–Cl system (LSiPSCl) shows the highest lithium ionic conductivity among the Li ion conductors reported to date. With the aim of establishing a large-scale production process for LSiPSCl, we report the development of a liquid-phase approach to its synthesis. The ionic conductivity and particle morphology are characterised, and their effects on the electrochemical properties of the LSiPSCl phase synthesised by the new liquid-phase method (L-LSiPSCl) are investigated. An L-LSiPSCl phase with an ionic conductivity of 6.6 mS cm −1 at 298 K is obtained by adjusting the sulfur ratio in the dissolved starting materials. Compared with the LSiPSCl phase synthesised via the conventional solid-state approach (S-LSiPSCl), L-LSiPSCl shows an increased grain-boundary resistivity and its particles consisted of small porous grains. An all-solid-state cell prepared using L-LSiPSCl as the solid electrolyte exhibits stable cycling, with a discharge capacity retention of >97% after 100 cycles; this is a comparable performance to that of the S-LSiPSCl-based reference cell, indicating that L-LSiPSCl functions stably as a solid electrolyte in all-solid-state batteries. Finally, this study suggests that liquid-phase synthesis is a promising approach for the large-scale production of sulfides that exhibit high ionic conductivities, such as LSiPSCl.